FAKTOR–FAKTOR YANG BERKAITAN DENGAN ALIH FUNGSI LAHAN SAWAH DI KECAMATAN PURWASARI KABUPATEN KARAWANG PROVINSI JAWA BARAT - Ade Irawan; Trisna Insan Noor; Tuti Karyani (Universitas Galuh, 2023)
Indonesia is an agricultural country where most of the land area used for agriculture is approximately 74.52% of the total land in Indonesia. The conversion of agricultural land is an issue that needs attention because of the community's dependence on the agricultural sector, especially food. In the activity of land conversion, it is closely related to the demand and supply of land, where the supply or supply of land is very limited while the demand for land is not limited. The research was conducted in Purawasari District, Karawang Regency, which is the sub-district with the largest area of land conversion in Karawang Regency. The purpose of this study was to determine the factors most related to the conversion of paddy fields in Purwasari District, Karawang Regency. The research design used descriptive qualitative with a sample size of 50 farmers. The results of the analysis of factors related to land use change are farmer education, farmer age, neighbor influence, investor influence, environmental conditions, government policies, land ownership area and inheritance system. The most dominant factors related to land conversion in Purwasari District, District Karawang is the area of land ownership and the age of the farmer